FT-IR Spectroscopic and Some Thermal Properties of Hofmann-Type Clathrate and Transition Metal Complexes of 2-Aminothiazole - Tufan, Y.; Kilicer, C.; Kormali, F. (Asian Journal of Chemistry, 2010)
In this study, new Hofmann type transition metal complexes of the form M(2-aminothiazole)2Ni(CN)4 (M = Mn, Fe, Co, Ni, Cu, Zn, Cd) and Cd(2-aminothiazole)2Ni(CN)4·C6H6, Hofmann type clathrate, have been prepared in powder form and their infrared spectra and some thermal decomposition properties of the clathrate are reported. The spectral and thermal data show that the structures of these complexes and the clathrate are analogous with related Hofmann type complexes. The observed n(C-N) wave numbers of the complexes are in good agrement with Irving-Williams natural stability series.